Releasing cation diffusion in self-limited nanocrystalline defective ceria thin films. Issue 23 (1st March 2017) - Esposito, V.; Ni, D. W.; Sanna, S.; Gualandris, F.; Pryds, N.
Abstract : Acceptor-doped nanocrystalline cerium oxide thin films are mechanically constrained nano-domains, with film/substrate interfacial strain and chemical doping deadlock mass diffusion. Abstract : Acceptor-doped nanocrystalline cerium oxide thin films are mechanically constrained nano-domains, with film/substrate interfacial strain and chemical doping deadlock mass diffusion. In contrast, in this paper we show that chemical elements result in highly unstable thin films under chemical reduction, with unexpected diffusion-driven effects such as fast migration of grain boundaries, porosity nucleation, and interdiffusion at low temperatures.